Stigma associated with sexually transmitted infections among patients attending suraksha clinic at a tertiary care hospital in northern India - Swastika Suvirya; Mukesh Shukla; Sucheta Pathania; Gopa Banerjee; Ajit Kumar; Adarsh Tripathi (Wolters Kluwer Medknow Publications, 2018)
Context: Illnesses affecting sexual organs and its correlation with improper sexual behavior lead to a negative attitude and discriminating behavior towards people affected by such disorders. Aim: The aim was to study the stigma associated with sexually transmitted infections (STIs) among patients attending Suraksha clinic at a tertiary care hospital in northern India. Settings and Design: This was a hospital-based cross-sectional study. Subjects and Methods: The present study was conducted at Suraksha (STI) clinic, King George's Medical University, Uttar Pradesh. A total of 487 STI patients (clinically and/or laboratory-confirmed) were contacted telephonically, of which 49 finally participated in the study. Stigma was assessed using modified and pretested version of India HIV-related stigma scale adapted in context to sexually transmitted diseases. Statistical Analysis: Quantitative variables were expressed as mean with standard deviation, and independent sample t-test was used to compare the mean values. P < 0.05 was considered statistically significant. Results: Mean scores of enacted, vicarious, felt normative, and internalized stigma for 49 patients (out 487) who finally participated in the study were 0.04±0.11, 0.55±0.70, 1.21±0.96, and 0.86±0.67, respectively. Unmarried/divorced/separated patients had significantly higher vicarious and felt normative stigma scores as compared to married individuals. Mean score for felt normative stigma was significantly higher among homosexual/bisexuals in comparison to heterosexual individuals. Conclusions: Efforts should be directed towards the provision of integrated services through sexual health-oriented campaigns to address the stigma associated with STI in a more comprehensive way.